Route Reliability Modelling in Mobile ad hoc Network (R2M2) model using Bayesian algorithm - Sharma, Pankaj Kumar; Kohli, Shruti; Sinha, Ashok K (Discoveries in Agriculture and Food Sciences, 2014)
Mobile ad-hoc network technology has gained popularity in recent years by researchers on account of its flexibility, low cost and eases of deployment. The objective of proposed R2M2 model is to evaluate the performance of MANET (Mobile ad hoc Network ) operating with DSR( Dynamic Source Routing) as routing protocol. The R2M2 model for MANET is simulated and implemented using network simulator ns 2.34 and validated using Bayesian rules. The R2M2 model is able to find out the probability of having certain behavior (able to decide reliable or not reliable) of routes, in uncertain observations (not able to decide whether the route is reliable or not) in presence of drop and delay. For performance evaluation of MANET using the proposed R2M2 model input variables (like node density, number of active connections, duration of communication, node movement speed, pause time & data transfer rate etc. ) and output variables drop rate and delay have been taken as output variables. The R2M2 model helps in deciding the certain and uncertain behavior of routes and consequently the nodes and is found satisfactory.